Assessing the importance of plant, soil, and management factors affecting potential milk production on organic pastures using regression tree analysis. (April 2020) - Zegler, Chelsea H.; Renz, Mark J.; Brink, Geoffrey E.; Ruark, Matthew D.
Abstract: Certified organic dairies are required to utilize pastures for a portion of forage intake. Pasture species composition, management, and soil fertility are known to influence milk production, but have not been studied concurrently. We evaluated agronomic and management variables on 20 organic dairies in the upper midwestern United States to determine factors associated with potential pasture milk production. At each farm, two pastures were sampled just prior to grazing in June and September for species composition, productivity, and forage nutritive value. Soil samples and management information were collected in October. Potential milk production was calculated based on forage productivity, cell wall concentration and digestibility, and estimated dry matter intake by a 500 kg cow. A regression tree prioritized the factors associated with potential milk production. Improved legume cover exceeding 40% in June increased potential milk production by 97%. Non-improved grass cover <70% in June and September increased potential milk production by >75%. Maintaining residual sward height at 9 cm or greater throughout the year was also associated with increased milk production. Soil fertility explained little of the variability in milk production. Our results suggest prioritizing management of residual height and improved legume and non-improved grass cover are critical for high milk production from organic pastures in the Upper Midwest. Highlights: Of the species measured, the cover of improved legumes and non-improved grasses were most associated with milk production. The sole management factor found to be associated with greater potential milk production was residual sward height. Slope of the pasture was the only soil characteristic found to have a significant effect on potential milk production.